A Single Step in vitro Bioassay Mimicking TLR4-LPS Pathway and the Role of MD2 and CD14 Coreceptors - Jagtap, Pramod; Prasad, Puja; Pateria, Abhishek; Deshmukh, Sachin D.; Gupta, Shalini (Frontiers in Immunology, 2020)
Acute systemic Gram-negative bacterial infections are accompanied by release of lipopolysaccharide (LPS) endotoxins into the bloodstream and an innate immune host response via the well-known toll like receptor 4 (TLR4) pathway. In this, LPS associates non-covalently with TLR4 to form an activated heterodimer (LPS/MD2/TLR4)2 complex in vivo, assisted by a coreceptor CD14. This complexation process has been illustrated ex vivo using indirect methods such as cytokine, interleukin, TNF-∝ measurements and by direct demonstration of sequential binding events on a surface using advanced optics. We are the first ones to carry out homogeneous self-assembly of LPS-rTLR4-MD2 conjugates in vitro in a single step, and further demonstrate the role of CD14 as a catalyst during this process. The assay comprises of LPS, MD2, CD14 and recombinant TLR4-conjugated magnetic particles co-incubated in a buffer at room temperature. The complexes are removed by magnetic separation and the extent of binding is estimated by quantifying the unbound biomolecules in the supernatant using standard biophysical techniques. Our results show that rTLR4-MD2-LPS complexes form in an hour and follow a 1:1:1 stoichiometry, in agreement with the in vivo/ex vivo studies. The assay is also highly specific; addition of known LPS-binding ligands decreased the LPS-rTLR4 complexation, allowing its use as a rapid tool for molecular inhibitor screening.